2017
DOI: 10.1124/mol.117.109678
|View full text |Cite
|
Sign up to set email alerts
|

Teaching an Old Drug New Tricks: Agonism, Antagonism, and Biased Signaling of Pilocarpine through M3 Muscarinic Acetylcholine Receptor

Abstract: Pilocarpine is a prototypical drug used to treat glaucoma and dry mouth and is classified as either a full or partial muscarinic agonist. Here, we report several unexpected results pertaining to its interaction with muscarinic M3 receptor (M3R). We found that pilocarpine was 1000 times less potent in stimulating mouse-eye pupil constriction than muscarinic agonists oxotremorin-M (Oxo-M) or carbachol (CCh), although all three ligands have similar values for M3R. In contrast to CCh or Oxo-M, pilocarpine does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The experimental system in these studies was different in comparison with our study (anesthetized rats vs acute mouse brain slices). However, we could speculate that possible causes of the discrepancies might be linked to differential activation of muscarinic receptor subtypes and cell-specific biased signaling obtained with different cholinergic agonists; for instance, pilocarpine shows more pronounced selectivity for the M3 vs M1 receptors in comparison with McN-A-343 (Mitchelson, 2012;Pronin et al, 2017). Additionally, this could be coupled to different modifications of excitability, with more sustained and profound hyperexcitability that could induce remodeling of neuronal circuits, leading, for example, to increased extracellular K + buffering that would inhibit CSD (Guedes and Cavalheiro, 1997;Koroleva and Bures, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental system in these studies was different in comparison with our study (anesthetized rats vs acute mouse brain slices). However, we could speculate that possible causes of the discrepancies might be linked to differential activation of muscarinic receptor subtypes and cell-specific biased signaling obtained with different cholinergic agonists; for instance, pilocarpine shows more pronounced selectivity for the M3 vs M1 receptors in comparison with McN-A-343 (Mitchelson, 2012;Pronin et al, 2017). Additionally, this could be coupled to different modifications of excitability, with more sustained and profound hyperexcitability that could induce remodeling of neuronal circuits, leading, for example, to increased extracellular K + buffering that would inhibit CSD (Guedes and Cavalheiro, 1997;Koroleva and Bures, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, M1 receptors were detected in the thecal cells of rat ovarian follicles as well as in cells of the corpus luteum on proestrus day, and it was demonstrated that ovulation demands the activation of these receptors in the left ovary [40]. In vitro studies performed on Chinese hamster ovary (CHO)-K1 cells indicated no response to cholinergic stimulation [41]. Meanwhile, overexpressing M1 receptors or M3 receptors in CHO cells determined a similar intracellular calcium increase in response to pilocarpine, a partial agonist for muscarinic receptors, or to carbachol [41].…”
Section: Gpcrs Activated By Neurotransmitters In Ovarian Cancermentioning
confidence: 99%
“…In vitro studies performed on Chinese hamster ovary (CHO)-K1 cells indicated no response to cholinergic stimulation [41]. Meanwhile, overexpressing M1 receptors or M3 receptors in CHO cells determined a similar intracellular calcium increase in response to pilocarpine, a partial agonist for muscarinic receptors, or to carbachol [41]. The study of Pronin and colleagues [41] is very important to understand that studies on non-tumorigenic ovarian cell lines should be considered with caution, as some of them do not respond to cholinergic stimulation.…”
Section: Gpcrs Activated By Neurotransmitters In Ovarian Cancermentioning
confidence: 99%
“…Muscarinic ACh receptors are widely expressed throughout the body, including in the gut, brain, eye, heart, vasculature, etc. [20,21,22,23,24,25,26,27,28]. In particular, CHRM1 and CHRM3 are robustly expressed in the gastrointestinal (GI) tract.…”
Section: Muscarinic Acetylcholine (Ach) Receptorsmentioning
confidence: 99%